Analisis dampak merger terhadap harga saham, abnormal return, dan volume perdagangan saham - Febriani, Lisa; Setiawan, Romi Adetio (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The process of merger involves the combination of two or more companies to form a single entity. Corporate mergers have the potential to impact the prices of securities such as stocks and bonds issued by the involved companies. This research aims to analyze the differences in stock prices, abnormal returns, and stock trading volumes before and after the merger of Bank Syariah Indonesia over a period of five days before the merger announcement and five days after the announcement. The research methodology adopts the event study approach and utilizes purposive sampling, considering the entire relevant population as the research sample. The Shapiro-Wilk normality test is employed to examine the data distribution, and the Paired Sample T-Test statistical analysis is used to test the differences between two distinct time periods: before and after the merger announcement. The findings of this study reveal that there are no significant differences in stock prices, abnormal returns, and stock trading volumes before and after the merger of Bank Syariah Indonesia. Therefore, it can be concluded that the merger does not have a significant impact on stock prices, abnormal returns, and stock trading volumes within the examined period.